Perancangan Board Game sebagai Media Pembelajaran Bahasa Minangkabau untuk Anak Sekolah Dasar - Reviana Ardila; Aryoni Ananta; Izan Qomarats (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
Indonesia is a country known for its linguistic diversity, which is considered one of its national treasures. Recently, the use of the Minangkabau language has experienced a significant decline. This design is created to help foster interest in learning the Minangkabau language among elementary school students. In the field of Visual Communication Design, designing creative educational media to enhance student interest and engagement, as well as introduce local culture, can be realized through the design of a board game. The design process includes data collection through questionnaires, interviews, and analysis using the 5W+1H method. The designed board game incorporates elements that teach Minangkabau vocabulary, phrases, and sentences, as well as introduce Minangkabau culture through interactive gameplay. The design results in a mascot, board game, logo, playing pieces, and a media mix from the TITAH board game design. It is hoped that this board game can serve as an effective and engaging alternative learning medium to preserve the Minangkabau language and culture among the younger generation.